2019
DOI: 10.1007/s42770-019-00221-z
|View full text |Cite
|
Sign up to set email alerts
|

Tibouchina granulosa (Vell.) Cogn (Melastomataceae) as source of endophytic fungi: isolation, identification, and antiprotozoal activity of metabolites from Phyllosticta capitalensis

Abstract: Endophytes are microorganisms that form symbiotic relationships with their own host. Included in this group are the species Phyllosticta capitalensis, a group of fungi that include saprobes that produce bioactive metabolites. The present study aimed to identify the cultivable endophytic fungal microbiota present in healthy leaves of Tibouchina granulosa (Desr.) Cogn. (Melastomataceae) and investigate secondary metabolites produced by a strain of P. capitalensis and their effects against both Leishmania species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 66 publications
0
5
0
2
Order By: Relevance
“…[17] Thus, the presence of endophytic fungi can provide host plants with several benefits, such as resistance to attack by herbivores, heat and drought, in addition to promoting growth and increasing nutrient recycling. [18 -20] According to Azevedo, [20] endophytic microorganisms can be found in the tissues of all plants studied around the world, including those in tropical forests, [7] coastal forests, [21] deserts, [22] Brazilian savannas, [23] tundra, [24] mangroves, [25] Antarctica, [26] the Arctic region, [27] Pantanal, [28] and prairies. [29] Some works have reported that secondary metabolites of fungi are also produced by the respective host plant, which may be related to a horizontal transfer of genes that may have occurred during the co-evolution between the endophytic fungus and the host plant.…”
Section: Endophytic Fungimentioning
confidence: 99%
See 3 more Smart Citations
“…[17] Thus, the presence of endophytic fungi can provide host plants with several benefits, such as resistance to attack by herbivores, heat and drought, in addition to promoting growth and increasing nutrient recycling. [18 -20] According to Azevedo, [20] endophytic microorganisms can be found in the tissues of all plants studied around the world, including those in tropical forests, [7] coastal forests, [21] deserts, [22] Brazilian savannas, [23] tundra, [24] mangroves, [25] Antarctica, [26] the Arctic region, [27] Pantanal, [28] and prairies. [29] Some works have reported that secondary metabolites of fungi are also produced by the respective host plant, which may be related to a horizontal transfer of genes that may have occurred during the co-evolution between the endophytic fungus and the host plant.…”
Section: Endophytic Fungimentioning
confidence: 99%
“…In previous studies, we reported the potential of endophytes against several types of microorganisms, including protozoa [7] and bacteria, [8] and described the main compounds produced, such as linoleic acid, [7] mellein and β-orcinaldehyde, [44,45] kojic acid, α-cyclopiazonic acid, and 20,25-dihydroxyaflavinine. [46] Thus, the study of the endophyte-host relationship can establish alternative sources of substances of biotechnological interest.…”
Section: Endophytic Fungimentioning
confidence: 99%
See 2 more Smart Citations
“…except for Tibouchina granulosa which was found to be colonised endophytically by a non-identified strain of Colletotrichum sp. in Brazil (Golias et al, 2020). Tools are never transferred between plant species and are always sterilised prior to every treatment as a precaution, preventing the transfer of the endophytically grown pest.…”
Section: Surveillance Informationmentioning
confidence: 99%